2014
DOI: 10.1186/1478-7547-12-23
|View full text |Cite
|
Sign up to set email alerts
|

Health research priority setting in selected high income countries: a narrative review of methods used and recommendations for future practice

Abstract: Research priority setting aims to gain consensus about areas where research effort will have wide benefits to society. While general principles for setting health research priorities have been suggested, there has been no critical review of the different approaches used. This review aims to: (i) examine methods, models and frameworks used to set health research priorities; (ii) identify barriers and facilitators to priority setting processes; and (iii) determine the outcomes of priority setting processes in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(139 citation statements)
references
References 18 publications
2
117
0
11
Order By: Relevance
“…Ultimately, the strength of this work is the involvement of a broad base of different stakeholders throughout the decision-making process, to develop much needed priorities for research in this under-recognised condition. The involvement of healthcare professionals, patients and carers not only increases the credibility and transparency of the final output as has been recognised in many other prioritisation processes [25,26] but also ensures that these priorities are relevant and feasible. It was clear that there were disparities in the research themes proposed by the patient and healthcare professional groups but this reflected their differing experiences of EC.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, the strength of this work is the involvement of a broad base of different stakeholders throughout the decision-making process, to develop much needed priorities for research in this under-recognised condition. The involvement of healthcare professionals, patients and carers not only increases the credibility and transparency of the final output as has been recognised in many other prioritisation processes [25,26] but also ensures that these priorities are relevant and feasible. It was clear that there were disparities in the research themes proposed by the patient and healthcare professional groups but this reflected their differing experiences of EC.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings suggest development of a research agenda by researchers alone may not meet needs across all constituencies. Multidisciplinary, multi-stakeholder approaches are desirable to capture holistic requirements (Bryant et al, 2014). Notably, slightly different pictures were seen when inferring priorities from respondents' actual recent needs versus broad future projection, which requires greater cognitive processing.…”
Section: Discussionmentioning
confidence: 99%
“…Bryant et al. in his narrative review of health research priority setting methods, models and frameworks found that, among eleven different priority setting exercises identified from Australia, the United Kingdom, the United States and Canada, none had been evaluated to assess the process employed or the extent to which the exercise had achieved its goals …”
Section: Methodsmentioning
confidence: 99%